1995
DOI: 10.1016/0022-3115(94)00406-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of particle fueling and plasma wall interactions on DIII-D discharges

Abstract: Portions of this document may be illegible in electronic image products. lmages are produced from the best available original. document.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Particle confinement is difficult to measure directly in devices such as DIII-D with a divertor configuration, and a discussion of particle confinement is beyond the scope of this paper. Previous work in DIII-D has shown that the ELM free global particle confinement time is of the same order as the energy confinement time [9,10]. Changes in particle confinement time during ELMing CDH-mode have not yet been measured or calculated.…”
Section: Discussionmentioning
confidence: 99%
“…Particle confinement is difficult to measure directly in devices such as DIII-D with a divertor configuration, and a discussion of particle confinement is beyond the scope of this paper. Previous work in DIII-D has shown that the ELM free global particle confinement time is of the same order as the energy confinement time [9,10]. Changes in particle confinement time during ELMing CDH-mode have not yet been measured or calculated.…”
Section: Discussionmentioning
confidence: 99%
“…Graphite-based first-wall components have been designed and tested to sustain particle and heat exhausts under steady-state conditions in Tore Supra [9] and DIII-D [10]. HT-7 is a superconducting tokamak [11] with the limiter configuration designed to operate with high power and long-duration discharge.…”
Section: Introductionmentioning
confidence: 99%
“…The graphite based first wall components have been designed and tested to sustain particle and heat exhausts under steady state conditions in Tore Supra [18].A major part of DIII-D [19] program is focused upon high performance experiments. HT-7 is a superconducting tokamak [20] with the limiter configuration designed to operate with high power and long duration discharge.…”
Section: Introductionmentioning
confidence: 99%